POLITICAL SHAMANS IN A FOUCAULDIAN PERSPECTIVE: HOW SHAMANS REMAIN PRESENT IN POLITICAL CONTESTATION - Anggi Fransiska Putri (SOSIOEDUKASI, 2026)
This article is not explaining how scientifically shamans are able to smooth the way for candidates in winning electoral politics, but rather this article aims to explain how the formation of discourse is built to support the rationality of political shamans so that there are still many who trust and use their services. Using the object of study at the moment of the election of the village head (pilkades) in Pangro Village in Central Java, the Foucauldian analysis attempts to examine the foundation of knowledge why shamans can have the role of "political consultants" in the midst of the current of modernity that relies on logical reasoning in the work of electoral political victory. The results of the study show, based on the genealogy of knowledge tracking, the rapid flow of modernity does not necessarily eliminate shamanism, but this rationality is transformed so that mystical reasoning can still exist following modern reasoning today. Likewise, the archaeological search of knowledge, which shows that traces of knowledge supporting the existence of shamans are still scattered quite dominant in the culture of the community so that their existence does not disappear, but rather has a strong place in people's beliefs, especially for the village community and candidates in the elections. This study concludes that mystical rationality is supported by citizen knowledge, which is maintained continuously in the local culture.